Non-structural carbohydrate status in Norway spruce buds in the context of annual bud structural development as affected by acidic pollution - Svobodová, H; Lipavská, H; Albrechtová, J (Environmental and experimental botany, 2000)
The present study focused on changes in the annual dynamics of the contents of non-structural saccharides (NSS) of Norway spruce vegetative buds related to their structural development under the effect of acidic pollution during the year 1995. Two types of material were analysed: (1) 4-year-old trees treated for 2 years by simulated acid rain (SAR; pH 2.9 and 3.9), and (2) 40-60-year-old trees growing in natural mountain stands exhibiting different degrees of macroscopic damage. Our study revealed that the dynamics of the NSS content reflected the major morphogenetic and developmental changes occurring during the annual bud developmental cycle. No systematic changes in the annual dynamics of NSS content were observed in buds from both mountain sites, or as a consequence of the SAR. The total sugar content of bud tissues was composed of a combination of five main sugar components: sucrose, glucose, fructose, raffinose family oligosaccharides (RFO; combination of raffinose and stachyose), and a pinitol fraction (PF) probably of cyclitols with pinitol as a main member. The dynamics of individual sugar components also reflected possible carbohydrate mediated bud frost protection. Interesting results were obtained from buds in dormant state. In dormant buds of the SAR experiment the higher value of the ratio PF:RFO of the pinitol fraction and raffinose family oligosaccharides followed the higher dose of SAR treatment. When evaluating the ratio from both types of material we assumed that changes in PF:RFO ratio corresponded to early stages of damage or acute metabolic reaction. Thus, we suggest the ratio PF:RFO as a possible non-specific metabolic marker of early bud stress reaction which is, among other stress factors, sensitive to increasing load of acidic pollutants.